Tingkat Kepercayaan Masyarakat terhadap Transparansi Keuangan dalam E Government Kota Bandung: The Level of Public Trust in Financial Transparency in E-Government in Bandung City - Arwati, Dini; Latif, Dini Verdania (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2019)
The Indonesian government is currently trying to implement e government in every gov- ernment organization. E government is a system based on technology and information that aims to improve the functions of public administration and relations with the commu- nity. With the e-government, it is expected to create information transparency, especially financial information. A transparent system can prevent misuse of the budget, which has a high level of corruption. The survey results at the global level indicate that corruption cases have caused mistrust of the government. This study aims to determine the level of public trust in financial transparency in e government. The research method used was a descriptive method by distributing questionnaires to 200 Bandung residents. The results of the study indicate that financial transparency in e government has an effect on public trust.